IMPLEMENTASI KERJA SAMA SISTER CITY BANDUNG - SEOUL DI BIDANG EKONOMI PERKOTAAN: Studi Kasus Peningkatan Kapasitas Sumber Daya Manusia Dalam Pengelolaan Pendapatan Daerah Pemerintah Kota Bandung Tahun 2016 - 2017 - Dewi Purbaningrum, (2023)
This study discusses the collaboration between the cities of Bandung, Indonesia and Seoul, South Korea in the field of urban economics. The Sister City collaboration between the city of Bandung and the city of Seoul is an inter-city government collaboration aimed at enhancing bilateral relations between the two cities which focus on cooperation in developing smart cities in the city of Bandung. This study discusses the implementation of cooperation between the cities of Bandung and the cities of Seoul in the field of urban economic development. By using descriptive qualitative research methods and interview research techniques and literature study in answering questions. In conducting the analysis the researcher used the concept of Sister City and the concept of capacity building. The results of the research explain that the collaboration between Bandung and Seoul is considered not to be running optimally due to differences in levels of government, language, lack of budget and COVID-19 pandemic.